Concentration threshold for polyethylene microplastics impacting nitrogen transfor-mation in heterotrophic nitrification-aerobic denitrification systems - Xue Bai; Mengying Yi; Lang Ran; Weidong Xiao; Ran Sun; Zherui Zhang; Sihai Hu; Yaoguo Wu (Bioresource Technology, 2027)

Disruption of retinol saturase enhances Polyunsaturated Fatty Acid (PUFA) biosynthesis in grass carp (Ctenopharyngodon idella) via upregulation of fads2 - Ru Zhang; Ran Yang; Jiang Zeng; Xiao Xiao; Houpeng Wang; Yongming Li; Xiaosi Wang; Jian Gao; Mudan He; Yonghua Sun (Aquaculture, 2027)

Heat transfer enhancement and entropy generation analysis of bionic fish-scale structures in narrow rectangular channels for plate-type fuel applications - Xiaoya Liu; Lingke Ran; Xinwen Zhao; Hongguang Xiao; Yongfa Zhang; Ming Ding (Annals of Nuclear Energy, 2026)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Purification of mariculture wastewater with antibiotics, heavy metals, and nitrite by AMF-IWS integrated constructed wetlands under salinity gradients - Zhouying Xu; Jianyun Zou; Tingrui Zhang; Kunyuan Xiao; Shengyun Huang; Zhiyao Ran; Xiangling Zhang; Yihui Ban (Journal of Water Process Engineering, 2026)

PFDA exposure promotes myocardial aging and fibrosis via hyperactivation of the MTORC1 signaling axis - Xiao Guang Chen; Ze Yu Liao; Yi Zhang; Ran Li (Food and Chemical Toxicology, 2026)

Toward integrated CO2 capture and photocatalytic conversion: From catalyst design to reactor engineering - Ziyi Li; Chenxi Ran; Jiao Feng; Jun Zhong; Jiaxin Xie; Yue-Fei Zhang; Xiao Luo; Yu Mao; Zhiwu Liang (Chemical Engineering Journal, 2026)

The interactive role of concentrated freshly squeezed tea juice supplementation on structural and in vitro digestibility of dried Nigari tofu - Mei-Xuan He; Ibrahim Khalifa; Xiao-Min Zeng; Jian Zheng; Wen Zhang; Zhu-Cheng Su; Noman Walayat; Ran Wei (Food Chemistry, 2026)

An assessment of direct steam sterilization on texture, flavor, and native functional proteins retention in yogurt - Julong Liu; Shusen Li; Ziqiang Li; Ran Xiao; Yong Guo; Erna Sun; Qiruonan Shen; Yuejiao Wang; Tingting Wang; Shuang Du; Wentao Zhang; Chenyuan Wang (Food and Bioproducts Processing, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Network pharmacology and cell experiments suggest natural algal astaxanthin as an anti-atherosclerotic agent via the PPARγ/NF-κB pathway - Yunmei Yin; Pei Wang; Zhen Zhang; Hongxiang Zhao; Meicong Xiao; Ran Chen; Kun Li; Shiqi Zhou; Rongqing Zhang (Algal Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Volatile methylsiloxanes in a textile dyeing and printing industrial park: Source profiles, ambient distributions and SOA formation potential - Xiaodie Pang; Hao Han; Wei Song; Xiangyu Zhang; Ran An; Jianqiang Zeng; Chao Peng; Weiqiang Yang; Chenshuo Ye; Xiao Tian; Hongcheng Lu; Zhou Zhang; et al. (Journal of Hazardous Materials, 2026)

C10–C12 aromatics dominate ozone and secondary organic aerosol formation potential in emissions from printed circuit board manufacturing - Xiaodie Pang; Wei Song; Weiqiang Yang; Chao Peng; Jianqiang Zeng; Zhou Zhang; Xiao Tian; Hongcheng Lu; Xiangyu Zhang; Ran An; Yang Li; Runcheng Zhu; et al. (Journal of Environmental Sciences, 2026)

The tautomerism induced by the number of hydroxyl groups in COFs and its contribution to thorium adsorption - Shangjie Zhao; Long Chen; Xiaofan Ding; Ke Wang; Jicong Li; Ran Zhang; Jing Zhao; Ke Ma; Jinping Liu; Songtao Xiao (Journal of Environmental Sciences, 2026)

Macrophage-targeted dual-responsive hollow mesoporous silica nanosystem for photothermal and immunomodulatory elimination of intracellular MRSA - Qiao Guo; Yongchao Yao; Jipeng Xiao; Xinyu Lu; Yiyuan Pu; Ran Li; Zhuo Zhang; Penghai Tang; Yuchen Jiang; Jianbin Luo (Chemical Engineering Journal, 2026)

Aboveground inputs rather than belowground root drive SOC responses to long term N addition in alpine grassland ecosystems of Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Juejie Yang; Ying Li; Yaoming Li; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; et al. (Agriculture, Ecosystems & Environment, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Permian A-type felsic magmatism in the South Tianshan Orogenic Belt: Crustal melting triggered by the Tarim mantle plume - Zhi-Hao Song; Xian-Tao Ye; Xiao-Qiang Liu; Hong-Ran Wang; Ming-Can Yang; Shun-Hao Fu; Chuan-Lin Zhang (Lithos, 2026)

Carbon and phosphorus regeneration during organic matter decomposition in aquatic ecosystems: characteristics, mechanisms, and environmental effects - Chao Yin; Yan Zeng; Jingan Chen; Peng Liao; Jia Yu; Guangrong Ran; Baohua Xiao; Xudong Guo; Ziyan Zhang; Jingfu Wang; Haiquan Yang; Quan Yuan (Geochimica et Cosmochimica Acta, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

New grylloblattid insect from the Lower Triassic Kayitou Formation of Yunnan Province, Southwest China - Shi-Xue Hu; Jin-Yuan Huang; Qi-Yue Zhang; Chang-Yong Zhou; Wen Wen; Xiao Min; Da-Ran Zheng; Qian-Qi Zhang (Palaeoworld, 2026)

Construction of Li1-xMn2O4-Pb composite electrode ESIX system for efficient lithium recovery from high-sodium sulfate-type lithium-precipitation mother liquor - Jialu Chen; Jiang Gao; Ran Zhang; Zirui Wang; Qiang Ren; Fengfeng Gao; Zhonglin Zhang; Xiao Du; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2026)

Source apportionment and health risk prioritization of groundwater contamination in a coal-mining area: An integrated SOM-PMF-Monte Carlo framework - Zheng Yin; Shiqi Zhang; Xiao Fu; Ran Sun; Ran Lv; Meng Yuan; Ziyuan Gao; Gang Wu (Journal of Environmental Management, 2026)

Experimental and numerical investigation of flow-induced vibration in CMC turbine blades using fluid-structure interaction - Maojing Ran; Lu Zhang; Zhe Liu; Xingshuang Wu; Tianhang Xiao; Xiguang Gao; Yingdong Song (Engineering Structures, 2026)

Interference of algal C-phycocyanin in type 2 diabetes: Mechanisms involving MAPK pathway activation and GLUT4 translocation - Hongxiang Zhao; Meicong Xiao; Yunmei Yin; Zhen Zhang; Yunyun Yang; Ran Chen; Kun Li; Pei Wang; Shiqi Zhou; Rongqing Zhang (Algal Research, 2026)

Dietary bamboo vinegar powder supplementation mitigates the adverse effects of a high-starch diet on growth performance, liver health, and glucose-lipid metabolism in largemouth bass (Micropterus salmoides) - Weibin Lai; Zhangyi Xiao; Ran Yu; Linyi Li; Wenqian Chen; Yuan Gao; Manqi Yang; Liangliang Zhang; Liming Lu; Jianchun Jiang (Frontiers in Marine Science, 2026)
This study explored the potential of bamboo vinegar powder (BVP) to mitigate hepatic injury and metabolic disturbance induced by a high-starch diet in largemouth bass ( Micropterus salmoides ). Fish were distributed into three groups (with three replicates per group) and fed for 56 days with a basal diet (BD), a high-starch diet (CSD), and the BVP-supplemented diet (CSDB, added 2.0 g/kg BVP to the CSD diet), respectively. After the feeding trial, fish in the CSD group exhibited a significant decrease in weight gain rate (WGR) and an increased hepatosomatic index (HSI) ( P < 0.05). Concurrently, hepatic glucose and lipid metabolism of fish in the CSD group were suppressed, leading to the accumulation of hepatic lipids and glycogen, along with histopathological manifestations such as hepatic vacuolation and nuclear shift. Furthermore, immune competence and hepatic antioxidant status were also compromised. However, relative to the CSD group, fish in the CSDB group demonstrated significant improvements in growth performance, immune function, and liver injury. Furthermore, BVP upregulated the expression of nuclear factor erythroid 2-related factor 2 ( nrf2 , a key regulator of antioxidant defense) and downregulated the nuclear factor kappa B ( nf - κb , a central transcription factor in inflammation) ( P < 0.05). More importantly, BVP might improve the metabolism of hepatic glucose and lipid in fish, by suppressing gluconeogenesis and promoting glycolysis to optimize glucose metabolism, as well as by inhibiting lipogenesis and promoting both lipid transport and catabolism to enhance lipid metabolism. Notably, dietary BVP supplementation significantly altered hepatic metabolite profiles, affecting pathways such as alpha-linolenic acid and arachidonic acid metabolism, and increasing the levels of several lipid metabolites, including docosahexaenoic acid and phosphatidylethanolamine species, compared to the CSD group ( P < 0.05). Collectively, these results demonstrated that BVP improved growth performance, liver health, and glucose-lipid metabolism in largemouth bass fed a high-starch diet.

Effects of Unloading Stress Variations on Mechanical and Acoustic Emission Properties of Rock Under Cyclic Loading - Yanhao Ning; Chunfeng Ye; Shiyue Zhang; Xiao Song; Jiajia Zhao; Xujing Tan; Qican Ran (Rock Mechanics and Rock Engineering, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Biodegradable microplastics-induced free-living nitrogen fixation enhancement and diazotrophic community differentiation in soils - Yujuan Han; Peixin Gao; Jiping Song; Yanning Li; Xiao Wang; Ning Yang; Xu Zhao; Bo Liu; Chuankun Zhang; Ran Li; Dan Wen; Ying Teng (Journal of Environmental Management, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Risk assessment, resistance monitoring and mechanism of field-evolved resistance to broflanilide in the tobacco cutworm, Spodoptera litura - Xiao Guo; Yilu Tong; Ren Li; Shengran Zhang; Daofeng Zhang; Cheng Qu; Xiaoli Ma; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

Tailored V/Mn/Ti ratio unlocks high-performance phosphate cathodes for sodium-ion batteries - Zhanhao Zhang; Xingjie Shao; Junjie Fan; Zhiyong Xiong; Yonglin Huo; Lei Ran; Hongcheng Lu; Wanxiu Xiao; Xitao lin; Hongdong Liu; Maowen Xu (Chemical Engineering Journal, 2026)

Exploring patterns and mechanisms of indigenous microbial community succession driven by polycyclic aromatics in heterotrophic nitrification and aerobic denitrification systems - Weidong Xiao; Yaoguo Wu; Lang Ran; Ran Sun; Sihai Hu; Zherui Zhang; Usman Ghani; Azhar Masaud; Maorui Zhang (Bioresource Technology, 2026)

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

A chlorinated 2-(2-phenylethyl)chromone in artificial agarwood as a DRD5 agonist and mediates the cAMP/Ca²⁺ signaling pathway to intervene in the growth and proliferation of gastric cancer cells - Zi-Xiao Jiang; Jian Feng; Wen-Cheng Hou; Mei-Ran Wang; Shu-Nan Zhang; Yang-Yang Liu (Phytochemistry Letters, 2026)

Bioinformatics-based discovery of a new norsesquiterpenoid from agarwood targeting CHRM2 and regulating the PI3K-Akt pathway in liver cancer - Zi-Xiao Jiang; Jian Feng; Wen-Cheng Hou; Mei-Ran Wang; Shu-Nan Zhang; Hao-Jie Liang; Yang-Yang Liu (Phytochemistry Letters, 2026)

Optimizing partial nitrification-anammox in a membrane aerated moving bed biofilm reactor for mainstream nitrogen removal - Xiao Ran; Yulong Yang; Zhihong Zheng; Hongyu Wang; Xingyu Zheng; Xiling Peng; Jie Yao; Minhua Wei; Shuang Zhang; Jin Xu (Journal of Environmental Chemical Engineering, 2026)

Recent advances in photocatalytic plastic degradation and upcycling: Catalysts, experiments, and mechanisms - Chenxi Ran; Ziyi Li; Yue-Fei Zhang; Xiao Luo; Zhiwu Liang; Yu Mao (Journal of Environmental Chemical Engineering, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

A multiscale risk operation and decision making model for inter-basin water diversion project under climate variability - Juan Chen; Zhen-ran Zhang; Yi-fan Liang; Xiao-hui Fan; Jian-qing Xie; Zhen Li; Ping-an Zhong (Environmental Research, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

CoAFNet: a correlation modelling and Attention Fusion Network for semantic change detection - Zhenni Li; Mengying Ran; Jingyi Liu; Shiming Hu; Hanquan Zhang; Dong Xiao (International Journal of Remote Sensing, 2026)

Comparative transcriptomics study reveals caste differentiation of the prepharyngeal gland in the ant Camponotus japonicus - W. Xu; P. Xiao; H. Ran; G. Zhang; Y. Xu; H. He (Insectes Sociaux, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Modeling battery electric vehicle users’ charging decisions in scenarios with both time-related and distance-related anxiety - Jiyao Wang; Wenbo Zhang; Xiao Luke Wen; Ran Tu; Dengbo He (Travel Behaviour and Society, 2026)

Resistance mechanisms and fitness outcomes of tetraniliprole, one novel diamide insecticide, in a near-isogenic strain of Spodoptera litura (Lepidoptera: Noctuidae) - Peng Lu; Ren Li; Xiao Guo; Juan Tang; Yilu Tong; Shengran Zhang; Qi Su; Cheng Qu; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

Flexible-rigid coupling configuration for advanced energy-sensing integrated microsystems - Chang-Liu He; Yao Tan; Hao Zheng; Cheng Tu; Xin-Ran Zhang; Dong-Ming Fang; Xu Zeng; Xiao-Sheng Zhang (Chemical Engineering Journal, 2026)

CD33 Isoform Splicing Dysregulation: A Molecular Determinant of Microglial Dysfunction in Alzheimer’s Disease Pathology - Xiao-Yan Li; Yu Zhang; Zhao Ran; Jia-Xin Luo; Xiao-Qin Yu; Mei-Hong Lu (Molecular Neurobiology, 2026)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Unveiling the efficacy of a novel strain of Beauveria brongniartii to manage Sitobion miscanthi (Takahashi) and Rhopalosiphum padi (Linnaeus) (Hemiptera: Aphididae) in China - Xujun Tian; Saige Zhu; Xiao Ran; Xinan Li; Xiangrui Li; Yunhui Zhang; Rongyu Li; Xun Zhu (Journal of Asia-Pacific Entomology, 2025)

Proteomic, metabolomic and lipidomic profiles provide insights on milk quality differences during heat treatment - Meiqing Chen; Ran Xiao; Shuang Du; Ashikur Rahman; Nan Zheng; Yangdong Zhang; Tianjiao Niu; Jiaqi Wang (Food Chemistry, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Targeted-nanoformulation of cannabidiol attenuates endothelial injury and platelet hyperactivation for combating silicosis - Sirong Chang; Yue Sun; Wenyue Zhang; Yi Guo; Huning Zhang; Nan Li; Ran An; Mengsi Xiao; Siwei Zou; Na Zhang; Kai Wang; Anning Yang; et al. (Chemical Engineering Journal, 2025)

Development of novel melatonin-isatin hybrids as multifunctional agents for Alzheimer’s disease - Ying-Ying Zhong; Jun‑Ze Deng; Qin Wang; Li Chen; Zi-Hang Yang; Ya-Mei Zhang; Lu‑Yi Zhou; Yi-Ran Li; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2025)

Dolomite reservoir differences in characteristics and controlling factors of grainstone shoal facies in Qixia Formation, Sichuan Basin - Benjian Zhang; Hualing Ma; Xiaojie Huang; Xihua Zhang; Xiao Chen; Fujie Jiang; Chen Xie; Yangui Chen; Ran Liu; Wei Wang; Haitao Sun (Carbonates and Evaporites, 2025)

A three-step process for purification and stability evaluation of analytical-grade phycocyanin from Spirulina - Hongxiang Zhao; Shilin Wu; Zhen Zhang; Ran Chen; Kun Li; Meicong Xiao; Yunmei Yin; Pei Wang; Rongqing Zhang (Algal Research, 2025)

Large-scale single tree information extraction of oil palm in Malaysia based on sub-meter visible light satellite images - Sen Zhang; Nan Li; Yaoping Cui; Jinwei Dong; Le Yu; Lishan Ran; Ziyue Chen; Jiqiang Niu; Wei Yan; Kasturi Devi Kanniah; Xiangming Xiao (Computers and Electronics in Agriculture, 2025)

Preparation of superhydrophobic melamine sponge based on in-situ polymerization for oil-water separation - Hongxia Zhang; Yaozhong Ran; Zhenyu Zhou; Fei Xiao (Process Safety and Environmental Protection, 2025)

Regulation of phytoplankton community by mesoscale eddies and the East Indian Coastal Current in the southwestern Bay of Bengal during the northeast monsoon - Hao Chen; Yuanli Zhu; Lihua Ran; Mengjia Zhang; Xiao Ma; Hongliang Li; Feng Zhou; W.N.C. Priyadarshani; Zhibing Jiang (Marine Environmental Research, 2025)

Semi-rational design enhances γ-glutamyltransferase transpeptidase activity for efficient L-theanine synthesis - Ran Zhang; Bo Jiang; Longbei Xiang; Licheng Zhou; Ziqun Xiao (Food Bioscience, 2025)

Response of nitrogen transformation and microbial community to aromatic compounds stress along heterotrophic nitrification and aerobic denitrification process - Weidong Xiao; Ran Sun; Lang Ran; Zherui Zhang; Xue Bai; Chen Lv; Maorui Zhang; Sihai Hu; Yaoguo Wu (Environmental Research, 2025)

Harnessing the power of lignin from Litsea cubeba fruit residues: Characterization and valorization - Kaili Zhang; Xiao Jiang; Ran Tao; Jingcong Xie; Jian Zhao; Ning Zhang; Yicun Chen; Yangdong Wang; Kui Wang; Jianchun Jiang (Biomass and Bioenergy, 2025)

The early Holocene vegetation history and quantitative reconstruction of climate in the Chahanur Lake, Inner Mongolia Plateau, China - Xu-Ran Zhang; Hua-Yong Zhang; Zhong-Yu Wang; Hao Chen; Xiao-Chang Wu; Zhao Liu (Palaeoworld, 2025)

LLTO-based electrodes for selective lithium extraction from high Mg2+/Li+ brines: Performance and mechanistic insights - Ran Zhang; Jialu Chen; Qian Xu; Beichen Sun; Xiao Du; Shanxia Luo; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2025)

Ensuring safe utilization of hydrochars in sustainable agriculture: Insights into the phytotoxicity and plant-promoting effects of low molecular weight organic compounds (LMWOCs) based on the untargeted metabolomics analysis - Weijie Xiong; Yuping Luo; Muyuan Zhang; Wei Sun; Yang Yang; Dan Song; Ran Xiao (Environmental Research, 2025)

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

Enzymatic and Non-Enzymatic decolorization of synthetic dyes using spent mushroom substrate - Wenjing Xiao; Ya Ran; Xinyu Guo; Yujun Dai; Zhilin Zhang; Jiashu Liu; Changchun Li (World Journal of Microbiology and Biotechnology, 2025)

Retraction Note: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Grazing mediates soil nutrient stocks through changing the plant functional composition and plant biomass allocation in alpine grassland - Fengcai He; Shikui Dong; Chunhui Ma; Xinghai Hao; Hao Shen; Juejie Yang; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Enhanced lignocellulose degradation and humification during the co-composting of cattle manure and tree branches: Synergism of microbial inoculation, biochar, and MnO2 - Wengao Shangguan; Muyuan Zhang; Shang Cheng; Dan Song; Yiyuan Wei; Mengjuan Wang; Xiaoxuan Su; Yuting Zhang; Ran Xiao (Process Safety and Environmental Protection, 2025)

CdS-mediated electron dynamics in light-assisted anaerobic digestion: Simultaneous cadmium sequestration and methane enrichment by alkali pretreatment - Baowei Zhang; Xiang Tang; Linrui Zhong; Jiangfu Zheng; Huannian Xiao; Yizhan Deng; Zezhong Ran; Mengqi Wei; Lifang Liu; Changzheng Fan (Journal of Hazardous Materials, 2025)

Effect of anticyclonic eddies on the production and emission of marine dimethylsulfide in the northern South China Sea - Jin-Wei Wu; Feng Xu; Shi-Bo Yan; Gao-Bin Xu; Yu-Cheng Jiang; Xiao-Ran Li; Xing Zhai; Li-Min Zhou; Hong-Hai Zhang; Zhao-Hui Chen (Global and Planetary Change, 2025)

Asymmetric C2-functionalization of indoles via visible-light-promoted three-component reaction - Han-Peng Pan; Xiao-Ying Hu; Jun-Hui Luo; Zhao-Jie Fu; Xin-Yi Yao; Meng-Yan Ran; Fang-Xin Wang; Xiang-Zhi Zhang (Molecular Diversity, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Effects of nitrogen deposition on temporal stability and resistance of the alpine steppe plant communities on the Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Bing Zhang; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; Ke Zhang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Rotational grazing can enhance the soil available nutrients rather than plant diversity to promote ANPP of alpine steppe - Fengcai He; Shikui Dong; Juejie Yang; Xinghai Hao; Chunhui Ma; Hao Shen; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

A novel fenton-like catalyst for efficient degradation of tetracycline: Application of the concept of “treating the wastes with wastes” - Lang Ran; Yajuan Zheng; Xu Zhang; Weidong Xiao; Lingxiao Zhu; Junlan Tang; Yaoguo Wu; Lincheng Zhou (Waste Management, 2025)

Influence of UHT processing and storage on the gastrointestinal fate and bioavailability of bovine milk proteins - Xing Li; Xiuxiu Zhang; Ran Xiao; Tianjiao Niu; Yuxiang Gu (Food Bioscience, 2025)

Trichothecroamides A‒F, antifungal amides from potato associated fungus Trichothecium crotocinigenum - Qiong Chen; Ao-Ran Xu; Bao-Bao Shi; Xiao-Fang Zhang; Ji-Kai Liu; Tao Feng (Phytochemistry, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

Evaluation of wood vinegar as a green carbon source for heterotrophic nitrification and aerobic denitrification process from performance, mechanism and potential - Weidong Xiao; Yaoguo Wu; Sihai Hu; Zherui Zhang; Lang Ran; Hongjian Luo; Ran Sun (Journal of Environmental Chemical Engineering, 2025)

Co-hydrothermal carbonization of lignocellulosic biomass and swine manure for humic substance abundant target products: Impacts of hydrothermal temperature and feedstock composition - Weijie Xiong; Muyuan Zhang; Yiyuan Wei; Dan Song; Yuping Luo; Jiangtao Wang; Shang Cheng; Ran Xiao (Journal of Environmental Chemical Engineering, 2025)

Short-term P addition weakens the positive effects of N addition on CH4 uptake in alpine grasslands of the Qinghai-Tibetan Plateau - Jiannan Xiao; Shikui Dong; Hao Shen; Ran Zhang; Hang Shi; Fencai He; Wei Li; Xiaoyan Li (Plant and Soil, 2025)

The growth performance in different seasons of Homatula variegata (Dabry de Thiersant, 1874) in Northern Guizhou, China - Gui Bang Xiao; Qi Wei Guo; Wei Xi Deng; Qi Qi Xiao; Lin Zhou; Hao Ran Zhang; Jia Lin; Ding Zhi Fang (Journal of Comparative Physiology B, 2025)

Isolation and identification of a novel bisacodyl analogue, bisacodyl dicycloproyl carboxylate, as a potential illegal additive in a dried plum product advertised for weight loss - Xian-Xian Li; Feng Jiang; Hong Yu; Xiao-Jing Huang; Jing-Xian Zhang; Jin-Tao Xia; Ying-ying Ran; Fan Huang; Jian Sun; Qing Hu (Food Additives & Contaminants: Part A, 2025)

Virtual screening and characterization of novel myogenic peptides from bovine collagen hydrolysates: Targeting myomaker - Hanfeng Li; Yunci Wang; Xiao Yong Ran; Qi Hao; Jianing Wang; Bing Zhang; Yanchuan Guo (Food Research International, 2025)

Response of bacterial community structure in saline soils to the application of kitchen waste-derived fermented organic fertilizer - Bin Xie; Wenzhuo Li; Tao Yang; Yajun Zhang; Weidong Xiao; Sihai Hu; Yaoguo Wu; Xiaofeng Sun; Bin wang; Ran Sun (World Journal of Microbiology and Biotechnology, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

High urea promotes mitochondrial fission and functional impairments in astrocytes inducing anxiety-like behavior in chronic kidney disease mice - Xi Zhao; Shengyao Zhang; Mengna Wu; Binyun Zhang; Guoran Wan; Meng Zhang; Jing Li; Zhuo Fei; Guoqi Zhu; Shaoqiu Jiang; Mohan Xiao; Wanjia Liu; et al. (Metabolic Brain Disease, 2025)

Indian ocean-type mantle domain in the Carboniferous Qushiman ophiolite in the Northern Pamir: Significance for the intra-oceanic subduction in the Paleo-Tethys Ocean - Yan Jing; Chuan-Lin Zhang; Chen Wang; Masumeh Sargazi; Zhi-Hao Song; Yi-kang Quan; Zhi-Kai Xu; Xiao-Qiang Liu; Hong-Ran Wang (Chemical Geology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Biochar enhanced co-composting for peat-free seedling substrate: A win-win solution for sustainable development of modern vegetable industry - Xiaoxia Fan; Yiyuan Wei; Dan Song; Ting Zhou; Ronghua Li; Xiaoxuan Su; Tao Zhang; Shang Cheng; Ran Xiao (Process Safety and Environmental Protection, 2025)

Immobilization and stabilization of D-allulose 3-epimerase for continuous D-allulose synthesis in packed-bed reactors - Ziqun Xiao; Bo Jiang; Jingjing Chen; Longbei Xiang; Ran Zhang (Food Bioscience, 2025)

A novel framework for dynamic and quantitative mapping of damage severity due to compound Drought–Heatwave impacts on tea Plantations, integrating Sentinel-2 and UAV images - Ran Huang; Yuanjun Xiao; Shengcheng Li; Jianing Li; Wei Weng; Qi Shao; Jingcheng Zhang; Yao Zhang; Lingbo Yang; Chao Huang; Weiwei Sun; Weiwei Liu; et al. (Computers and Electronics in Agriculture, 2025)

Impact of residual antibiotics on microbial decomposition of livestock manures in Eutric Regosol: Implications for sustainable nutrient recycling and soil carbon sequestration - Linfa Fang; Prakash Lakshmanan; Xiaoxuan Su; Yujia Shi; Zheng Chen; Yu Zhang; Wei Sun; Junxi Wu; Ran Xiao; Xinping Chen (Journal of Environmental Sciences, 2025)

RETRACTED ARTICLE: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Co-hydrothermal carbonization of lignocellulosic biomass and swine manure: Optimal parameters for enhanced nutrient reclamation, carbon sequestration, and heavy metals passivation - Weijie Xiong; Yuping Luo; Wengao Shangguan; Yue Deng; Ronghua Li; Dan Song; Muyuan Zhang; Zengyi Li; Ran Xiao (Waste Management, 2024)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

Construction of Bi5O7I/Bi3O4Br heterojunction with abundant oxygen vacancies to enhance photocatalytic performance - Jian Feng; Xia Ran; Li Wang; Bo Xiao; Keqin Zhang; Jinming Zhu; Zuoji Liu; Chaozhong Li; Xinai Cui; Rong Li; Guangwei Feng (Journal of Environmental Chemical Engineering, 2024)

Functionalized mesoporous biosilica for immobilizing D-allulose 3-epimerase: A multienzyme cascade strategy for calorie reduction in fruit tea drinks - Ziqun Xiao; Ran Zhang; Longbei Xiang; Bo Jiang; Jingjing Chen (Food Bioscience, 2024)

Environmental Persistent Free Radicals in highly polluted soils and the association with polycyclic aromatic compounds - Yongqiang Zhang; Yousong Zhou; Hanchen Wang; Kai Xiao; Zhihan Luo; Yaojie Li; Ran Xing; Ke Jiang; Donglei Fu; Wenxin Liu; Shu Tao; Guofeng Shen (Environmental Research, 2024)

Effects of oyster shell addition on shrimp aquaculture and the dynamic succession of surface biofilm microbial communities - Xianke Huang; Guoqiang Xiao; Xiang Zhang; Shuangshuang Teng; Min Li; Yilong Cai; Ran Chen; Xiaolin Huang (Frontiers in Marine Science, 2024)
Introduction In the context of Litopenaeus vannamei aquaculture, the incorporation of oyster shells has proven beneficial for enhancing water quality and the growth conditions of the shrimp. Nonetheless, the specific effects of in-situ water treatment using oyster shells on water quality and shrimp growth, along with the composition and succession dynamics of the microbial community within oyster shell biofilms, have yet to be thoroughly investigated. Methods This study established control, low-concentration, and high-concentration oyster shell addition groups to emulate the in-situ water treatment environment with oyster shells, with the objective of elucidating the impacts of oyster shell addition on the aquaculture setting. Results The results showed that the addition of oyster shells could significantly improve the length ( F = 12.248, P = 0.005 ), weight( F = 138.234, P < 0.001 ), and survival rate ( F = 15.248, P < 0.001 ) of shrimp, while there were no significant differences in the length ( F = -1.233, P = 0.267 ) and survival rate ( F = -2.143, P = 0.076 ) between the high and low concentration groups. Additionally, oyster shell addition resulted in elevated phosphate levels ( F = 74.92, P < 0.001 in Day 70), diminished nitrite levels ( F = 5.276, P = 0.031 in Day 56), and increased nitrate concentrations ( F = 9.421, P = 0.006 in Day 70). Within the biofilms, the relative abundances of Ruegeria, Tenacibaculum , BD2- 11_terrestrial_group , and Kapabacteriales exhibited significant declines over time, whereas the relative abundance of Nitrospira demonstrated a marked increase, ultimately emerging as the predominant bacterium (Relative abundance 31.8%) in the biofilms during the latter stages of the experiment. Nitrospira also exhibited a notably higher relative abundance in the microbial community of the experimental water group relative to the control group ( F = 2.265, P = 0.001 ). Discussion The biofilm provided conditions for the proliferation of Nitrospira , thereby accelerating the transformation of nitrite into nitrate in the aquaculture system, which subsequently improved the shrimp farming conditions. This research offers valuable insights for the application of oyster shells in shrimp farming and contributes to the theoretical underpinnings necessary for advancing our understanding of the mechanisms through which oyster shell biofilms enhance water quality and foster shrimp health.

Different responses of individuals, functional groups and plant communities in CSR strategies to nitrogen deposition in high-altitude grasslands - Xueqi Li; Ying Li; Hao Shen; Shuai Li; Zhenzhen Zhao; Jiannan Xiao; Ran Zhang; Hang Shi; Hui Zuo; Tu Danjia; Guoming Chen; Xueli Zhou; et al. (Science of The Total Environment, 2024)

Orbit-induced rainfall dipole pattern in South Asia over the past 425 ka - Gaowen Dai; Zhongshi Zhang; Guoqiao Xiao; Zongmin Zhu; Qing Yan; Ran Zhang (Quaternary Science Reviews, 2024)

Optimized ammonium-nitrate ratios in constructed wetlands for simultaneously efficient nitrogen removal and greenhouse gas reduction - Ling-Min Zhang; Ran Liu; Xiao-Qin Luo; Ying Liu; Xi-Qi Li; Qing-Jie Meng; Hong-Cheng Wang (Journal of Water Process Engineering, 2024)

Selective increase of antibiotic-resistant denitrifiers drives N2O production in ciprofloxacin-contaminated soils - Linfa Fang; Yue Deng; Prakash Lakshmanan; Weibing Liu; Xiufeng Tang; Wenxin Zou; Tong Zhang; Xiaozhong Wang; Ran Xiao; Jinbo Zhang; Xinping Chen; Xiaoxuan Su (Journal of Hazardous Materials, 2024)

Nonlinear effects of agricultural drought on vegetation productivity in the Yellow River Basin, China - Yujie Ding; Lifeng Zhang; Yi He; Shengpeng Cao; Andrei Gusev; Yan Guo; Ling Ran; Xiao Wei; Filonchyk Mikalai (Science of The Total Environment, 2024)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Deciphering the key factors affecting pesticide residue risk in vegetable ecosystem - Daiwei Liu; Tongtong Chen; Yahui Gong; Xuanjing Chen; Wei Zhang; Ran Xiao; Yuheng Yang; Tong Zhang (Environmental Research, 2024)

Customization of indium-based MOFs for enhanced adsorptive and photocatalytic of organic pollutants: Morphology involvement on performance and mechanism - Wenliang Zhang; Yan Wang; Timing Fang; Xiao Tang; Zhezheng Ding; Yunhai Han; Ran Guo; Pengfei Qi; Xiaomin Liu (Chemical Engineering Journal, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

B/N modified carbon nanofiber mesh covered with layered double hydroxide for large current overall water splitting - Ji Qi; Chunqi Zhu; Jianing Hu; Shuai Ran; Tauqeer Ahmad; Siraj Ullah; Lixu Chen; Yi Chen; Yuqing Xia; Xue Sun; Chuang Li; Xiao Chen; et al. (Fuel, 2024)

Exogenous sulfur application can effectively alleviate iron deficiency yellowing in peanuts and increase pod yield - Xiao-yan Zhang; Wen-feng Hou; Ze-chang Gou; Shu-ran Jia; Han Li; Qiang Gao; Xiao-yu Li (European Journal of Agronomy, 2024)

Fibroblast growth factor receptor 4 deficiency in macrophages aggravates experimental colitis by promoting M1-polarization - Luyao Shen; Cong Wang; Ran Ren; Xudong Liu; Dongqin Zhou; Yu Chen; Yu Zhou; Juan Lei; Yang Xiao; Nan Zhang; Huakan Zhao; Yongsheng Li (Inflammation Research, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Moving forward from escaping the poverty trap in China's greenest regions: Examining four decades of socioecological evolution to re-orient sustainable development policies - Xinhua Li; Chong Jiang; Yixin Wang; Jie Liu; Ran Wang; Ying Zhao; Jie Zhang; Haiyan Zhang; Buqing Wang; Yuexin Xiao (Applied Geography, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

Casein/butyrylated dextrin nanoparticles and chitosan stabilized bilayer emulsions as fat substitutes in sponge cakes - Han Tao; Xiao-Han Fang; Pin Chen; Bao-Qiu Yang; Ran Feng; Bao Zhang (Food Chemistry, 2024)

Mn-O bond Engineering Mitigating Jahn-Teller Effects of Manganese Oxide for Aqueous Zinc-ion Battery Applications - Meng Xie; Xiao Zhang; Ran Wang; Yang Jiao; Zhiwei Shu; Sunpeng Shan; Yuhong Bian; Hongjun Lin; Jianrong Chen; Yanchao Xu (Chemical Engineering Journal, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Reducing carbon and nitrogen loss by shortening the composting duration based on seed germination index (SCD@GI): Feasibilities and challenges - Ran Xiao; Lan Li; Yanye Zhang; Linfa Fang; Ronghua Li; Dan Song; Tao Liang; Xiaoxuan Su (Science of The Total Environment, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Meta-analysis addressing the potential of antibiotic resistance gene elimination through aerobic composting - Hongge Wang; Xuan Wang; Lu Zhang; Xinyuan Zhang; Yubo Cao; Ran Xiao; Zhaohai Bai; Lin Ma (Waste Management, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Gas-to-particle partitioning of atmospheric water-soluble organic aerosols: Indications from high-resolution observations of stable carbon isotope - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Xiao-Ying Yang; Tian Xie; Yu-Xian Zhang; Yongwen Xue (Atmospheric Environment, 2024)

Systemic evaluation of novel acaricide hexythiazox for bioactivity improvement and risk reduction at the enantiomer level - Ping Zhang; Furong Yang; Lulu Ran; Cancan Yang; Can Tang; Xiaojiang Ke; Juanni Chen; Wei Xiao; Lin He; Zhifeng Xu (Science of The Total Environment, 2024)

Methyl benzoate-related compounds as potential repellents and fumigants for the control of cigarette beetle, Lasioderma serricorne (F.) - Junli Xiao; Jianbo Jin; Shanyi Chen; Jianfeng Zhang; Peijian Cao; Li-Juan Mao; Ran Li (Journal of Stored Products Research, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Promoting nitrogen conversion in aerobic biotransformation of swine slurry with the co-application of manganese sulfate and biochar - Xuan Wu; Xinyu Zhao; Guorong Yi; Wanqiang Zhang; Runyu Gao; Daniel Kuok Ho Tang; Ran Xiao; Zengqiang Zhang; Yiqing Yao; Ronghua Li (Journal of Environmental Management, 2024)

A novel Zr-P-modified nanomagnetic herbal biochar immobilized Cd and Pb in water and soil and enhanced the relative abundance of metal-resistant bacteria: Biogeochemical and spectroscopic investigations to identify the governing factors and potential mechanisms - Yueru Fang; Ping Wang; Lan Zhang; Han Zhang; Ran Xiao; Yuan Luo; Kuok Ho Daniel Tang; Ronghua Li; Hamada Abdelrahman; Zengqiang Zhang; Jörg Rinklebe; Sang Soo Lee; et al. (Chemical Engineering Journal, 2024)

Construction of dual functional CuAl-LDHs nanocomposite loaded with IGF2BP3 siRNA for enhanced therapy of gastric cancer - Haiping Li; Yuying Zhang; Bo Huang; Feifei Yang; Qiang Ma; Xiaolin Wang; Yuying Liu; Junwu Ren; Xiaojuan Pan; Ce Liang; Shimin Wang; Hao Ning; et al. (Chemical Engineering Journal, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Spatiotemporal evolution of agricultural drought and its attribution under different climate zones and vegetation types in the Yellow River Basin of China - Yujie Ding; Lifeng Zhang; Yi He; Shengpeng Cao; Xiao Wei; Yan Guo; Ling Ran; Mikalai Filonchyk (Science of The Total Environment, 2024)

Different binding properties of odorant-binding protein 8 to insecticides in Orius sauteri - Zhe-Ran Wu; Yi-Wen Pei; Xiao-Qing Zhang; Min Lu; Xiao-Long Liu (Pesticide Biochemistry and Physiology, 2024)

Petrogenesis of the late Cenozoic potassium-rich volcanism in the NW Tibetan Plateau: Constraints on the mantle evolution through post-orogenic events - Masumeh Sargazi; Chuan-Lin Zhang; Zhi-Hao Song; Hong-Ran Wang; Zahid Hussain; Xian-Tao Ye; Wei Wang; Xiao-Fei Du (Lithos, 2024)

Micro formation mechanism of oil–water inversion in reservoirs based on water film theory—An example from the Dawangzhuang Oilfield in Bohai Bay Basin - Xiao Hu; Longchuan Pu; Aihua Ran; Jun Xie; Fengqun Li; Yuzong Cheng; Suhua Zhang; Zhe Li; Qiongyao Pu; Jialin Fu (Fuel, 2024)

Tumor microenvironment-activated hollow vanadium-based nanoplatform for precise therapy of lung cancer through synergistically reversing cisplatin resistance - Lang Ran; Jianmin Xiao; Weijie Zhang; Miaomiao Wang; Huan Xin; Huimin Li; Hong Hao; Maoyang Wang; Xiaofei Wang; Geng Tian; Guilong Zhang (Chemical Engineering Journal, 2024)

Storage, form, and influencing factors of karst inorganic carbon in a carbonate area in China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; et al. (Science China Earth Sciences, 2024)

A new cyclohexenone derivative from phomopsis sp. XM-01 - Cheng-Yao Wang; Dong Gan; Chen-Zhe Li; Li Zhu; Xiao-Ran Zhang; Ya-Ni Li; Xiu-Hong Wu; Hao Zhou; Le Cai (Natural Product Research, 2024)

Analysis of the contribution of rainfall to recharge in the Mu Us Desert (China) based on lysimeter data - Xuanming Zhang; Ning Wang; Linshun Cao; Bin Ran; Wenke Wang; Yu Xiao; Zaiyong Zhang; Da Xu; Zhoufeng Wang (Hydrogeology Journal, 2024)

Dryness stress weakens the sustainability of global vegetation cooling - Zilin Li; Xiaoyong Bai; Qiu Tan; Cuiwei Zhao; Yangbing Li; Guangjie Luo; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; Fengjiao Song; et al. (Science of The Total Environment, 2024)

Differences in background environment and fertilization method mediate plant response to nitrogen fertilization in alpine grasslands on the Qinghai-Tibetan Plateau - Shun He; Jianqing Du; Yanfen Wang; Lizhen Cui; Wenjing Liu; Yifan Xiao; Qinwei Ran; Linfeng Li; Zuopei Zhang; Li Tang; Ronghai Hu; Yanbin Hao; et al. (Science of The Total Environment, 2024)

Na2S-modified biochar for Hg(II) removal from wastewater: A techno-economic assessment - Wenwen Zhao; Zhongsheng Zhang; Yuan Xin; Ran Xiao; Feng Gao; Haitao Wu; Wenfeng Wang; Qiang Guan; Kangle Lu (Fuel, 2024)

Occurrence, distribution, and ecological risk of heavy metals and veterinary antibiotics in soils from citrus orchards: side effects of organic substitution - Pingping Ye; Kunpeng Gao; Hua Feng; Linfa Fang; Dong Li; Jong-Hwan Park; Yueqiang Zhang; Ran Xiao (Journal of Soils and Sediments, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Analysis of Stress–Strain Characteristics and Signal Coherence of Low-Specific-Speed Impeller Based on Fluid–Structure Interaction - Fengquan Qiao; Yi Sun; Di Zhu; Mingkun Fang; Fangfang Zhang; Ran Tao; Ruofu Xiao (Journal of Marine Science and Engineering, 2023)
In this study, an analysis of a low-specific-speed pump is carried out based on the methods of one-way and two-way fluid–structure interactions (FSIs). This study analyzes the influence of FSIs on the internal flow field and external characteristics of the pump. Utilizing a two-way FSI, the signal coherence analysis method is employed to analyze the coherence of signals between the flow field and the structural field. Addressing the issue of a lack of a connection between the two signals, this study bridges a gap in the existing research. The results indicate that different interaction methods have certain influences on impeller stress and deformation. However, in both coupling modes, the maximum deformation and the maximum equivalent stress have the same distribution position. The head error obtained using the two-way coupling method is lower than that of the uncoupled results, which indicates that the two-way FSI calculation results are closer to the experimental results. The pressure pulsation signals at the interface of the impeller and volute exhibit strong coherence with the structural field signals. For low-specific-speed centrifugal pumps, establishing a clear connection between the flow field signals and structural field signals will help guide further optimization of their performance through design.

Beany flavor in pea protein: Recent advances in formation mechanism, analytical techniques and microbial fermentation mitigation strategies - Longbei Xiang; Bo Jiang; Youling L. Xiong; Leon Zhou; Fang Zhong; Ran Zhang; Assam Bin Tahir; Ziqun Xiao (Food Bioscience, 2023)

Identifying cadmium and lead co-accumulation from living rice blade spectrum - Shuangyin Zhang; Teng Fei; Yiyun Chen; Jiaxin Yang; Ran Qu; Jian Xu; Xiao Xiao; Xuejun Cheng; Zhongzheng Hu; Xuedong Zheng; Dengzhong Zhao (Environmental Pollution, 2023)

Livestock grazing may weaken N deposition effects on soil C:N:P stoichiometry in alpine grassland of the Qinghai-Tibetan Plateau - Hao Shen; Shikui Dong; Shuai Li; Hanzhong Zheng; Qiyun Wang; Junxiang Liu; Jiannan Xiao; Hui Zuo; Ran Zhang; Xiuchun Yang (CATENA, 2023)

Inter-laboratory validation by event-specific qPCR methods for the detection of genetically modified insect and herbicide-tolerant maize DBN9501 - Jing Wang; Bing Xiao; Ruiying Zhang; Haitao Guan; Yang Yang; Yijia Ding; Ran Yuan; Xiaolei Zhang; Lingyan Li; Jingang Liang; Hongtao Wen (Journal of Consumer Protection and Food Safety, 2023)

Coarse cereals modulating chronic low-grade inflammation: review - Yongzhu Zhang; Esra Capanoglu; Linshu Jiao; Liqing Yin; Xianjin Liu; Ran Wang; Jianbo Xiao; Baiyi Lu (Critical Reviews in Food Science and Nutrition, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

In-situ introduction of CePO4 for stabilizing electrocatalytic activity of quasi-MOF with partially missing C≡N skeleton - Shuke Li; Meng Xie; Xiao Zhang; Nana Wang; Ran Wang; Yanchao Xu; Hongjun Lin; Yang Jiao; Jianrong Chen (Chemical Engineering Journal, 2023)

Sulfur-aided aerobic biostabilization of swine manure and sawdust mixture: Humification and carbon loss - Yang Wang; Jingwen Wang; Guorong Yi; Xuan Wu; Xiu Zhang; Xu Yang; Kuok Ho Daniel Tang; Ran Xiao; Zengqiang Zhang; Guangzhou Qu; Ronghua Li (Bioresource Technology, 2023)

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Spring photosynthetic phenology of Chinese vegetation in response to climate change and its impact on net primary productivity - Yingying Xue; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Min Liu; et al. (Agricultural and Forest Meteorology, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Correction to: dual role of endoplasmic reticulum stress-ATF-6 activation in autophagy and apoptosis induced by cyclic stretch in myoblast - Qiang Zhang; Guirong Liu; Ran Liu; Jun Liu; Xuemin Zeng; Dapeng Ren; Xiao Yan; Xiao Yuan (Apoptosis, 2023)

Optimization of runner and vane blade angle of an oscillating water column based on genetic algorithm and neural network - Jiahao Lu; Fangfang Zhang; Ran Tao; Xiaoqin Li; Di Zhu; Ruofu Xiao (Ocean Engineering, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

A versatile organic silicate aluminum hybrid coagulant for broad-spectrum removal of heavy metal ions - Jin-Wei Liu; Tao Fu; Guang-Dong Sun; Xiao-Ran Shen; Sheng Liu; Yang He; Yi Xu; Hua-Zhang Zhao (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Synergetic effect and mechanism of elementary sulphur, MgSO4 and KH2PO4 progressive reinforcement on pig manure composting nitrogen retention - Yang Wang; Jingwen Wang; Xuan Wu; Ran Zhao; Zengqiang Zhang; Juanjuan Zhu; Muhammad Azeem; Ran Xiao; Junting Pan; Xiu Zhang; Ronghua Li (Environmental Pollution, 2023)

Strategic tillage is a promising alternative to conventional and no-tillage: Evidence from a 12-year field trial in a double-cropped rice system - Xing Wang; Cong He; Bai-Jian Lin; Xin Zhao; Ran Zhang; Ling-Tao Zhong; Xiao-Ping Xiao; Hai-Lin Zhang (European Journal of Agronomy, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Fog event is possibly a source rather than a sink of atmospheric nitrate aerosols: Insights from isotopic measurements in Nanjing, China - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Zhu-Yu Zhao; Mei-Yi Fan; Xiao-Ying Yang (Applied Geochemistry, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Observed Taylor cap around a seamount intensified by a surface mesoscale eddy in the Northwest Pacific - Yansong Liu; Qiang Ren; Fei Yu; Jianfeng Wang; Ran Wang; Feng Nan; Yanan Ding; Tongtong Zheng; Chuanzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiao-Hua Zhu (Climate Dynamics, 2023)

Nitrate_dependent suberization regulates cadmium uptake and accumulation in maize - Anle Chen; Tong Liu; Yan Deng; Ran Xiao; Tong Zhang; Yuan Wang; Yuheng Yang; Prakash Lakshmanan; Xiaojun Shi; Fusuo Zhang; Xinping Chen (Science of The Total Environment, 2023)

Three new sesquilignans from the stems of Eleutherococcus senticosus and their bioactivities - Yue Zhang; Yi-Ming Zhao; Xiao-Jing Shao; Xue-Hui Wang; Tian-Tian Bei; Yi-Ran Jiang; Wen-Hui Xu; Hyun-Sun Lee; Meng-Xue Xiu; Jian Song; Long Cui (Phytochemistry Letters, 2023)

Terrigenous organic carbon contributes to reservoir carbon emissions: Potential role of the microbial community along a trophic gradient - Qiong Tang; Lunhui Lu; Fang Luo; Xinrui Li; Yuanyuan Zhang; Ran Li; Carolina Bernal; Solange Vera; Irina Izaguirre; Yan Xiao; Zhe Li (Journal of Hydrology, 2023)

Impacts of EDTA on the fate of nutrients and heavy metals during the hydrothermal carbonization of poultry manure - Xuhao Chen; Xiaoxia Fan; Kunpeng Gao; Yang Cheng; Ke Zhang; Liyuan Liu; Lingfa Fang; Jong-Hwan Park; Xinping Chen; Ran Xiao (Journal of Environmental Chemical Engineering, 2023)

Occurrence profiling and environmental risk assessment of veterinary antibiotics in vegetable soils at Chongqing region, China - Linfa Fang; Chengyu Chen; Fen Zhang; Esmat F. Ali; Binoy Sarkar; Jörg Rinklebe; Sabry M. Shaheen; Xinping Chen; Ran Xiao (Environmental Research, 2023)

Dual role of endoplasmic reticulum stress-ATF-6 activation in autophagy and apoptosis induced by cyclic stretch in myoblast - Qiang Zhang; Guirong Liu; Ran Liu; Jun Liu; Xuemin Zeng; Dapeng Ren; Xiao Yan; Xiao Yuan (Apoptosis, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

Efficient catalytic oxidation of chlorinated volatile organic compounds over RuO2-WOx/Sn0.2Ti0.8O2 catalysts: Insight into the Cl poisoning mechanism of acid sites - Feiyi Zhou; Qi Xin; Yujie Fu; Zhesheng Hua; Yi Dong; Mingchu Ran; Hao Song; Shaojun Liu; Ruiyang Qu; Yang Yang; Xiao Zhang; Chenghang Zheng; et al. (Chemical Engineering Journal, 2023)

pH and non-enzymatic glucose response at ultra-low concentration using submicrochannel heterogeneous membrane - Yuan-Ju Tang; Kai Cheng; Lin-Fang Tan; Xiao-Ting Xie; Bin Zhang; Wen-Ming Su; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

A new cyclopentenone derivative from Trichoderma atroviride HH-01 - Li Zhu; Jia-Peng Wang; Feng Hao; Dong Gan; Xiao-Ran Zhang; Chen-Zhe Li; Cheng-Yao Wang; Liang Zhang; Le Cai (Natural Product Research, 2023)

Time to reconsider the enigmatic tail of eastern Paleo-Tethys: New insights from Borneo - Xiao Ran Zhang; Sun-Lin Chung; Azman A. Ghani; Rezal Rahmat; Yi-Ju Hsin; Hao-Yang Lee; Ping-Ping Liu; Jinyu Xi (Lithos, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Optical Coherence Tomography in Cerebrovascular Disease: Open up New Horizons - Ran Xu; Qing Zhao; Tao Wang; Yutong Yang; Jichang Luo; Xiao Zhang; Yao Feng; Yan Ma; Adam A. Dmytriw; Ge Yang; Shengpan Chen; Bin Yang; et al. (Translational Stroke Research, 2023)

Fast asteroidal period inversion by parallel acceleration-based three-step reduced voting - Yong-Xiong Zhang; Xiao-Ping Lu; Tan Guo; Xin-Ran Li (Advances in Space Research, 2023)

Insights into carbon loss reduction during aerobic composting of organic solid waste: A meta-analysis and comprehensive literature review - Pingping Ye; Linfa Fang; Dan Song; Muyuan Zhang; Ronghua Li; Mukesh Kumar Awasthi; Zengqiang Zhang; Ran Xiao; Xinping Chen (Science of The Total Environment, 2023)

Three-dimensional structure of mesoscale eddies and their interaction with Kuroshio based on observations from a CPIES array - Qiang Ren; Yansong Liu; Ran Wang; Feng Nan; Jianfeng Wang; Xinyuan Diao; Zifei Chen; Fei Yu; Chuangzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiao-Hua Zhu (Frontiers in Marine Science, 2023)
Mesoscale eddies are widespread in the oceans; however, tracking and observing them remains a challenge. Additionally, there are few studies of eddy–Kuroshio interactions based on large-scale in situ data. Data from a large array of 39 CPIESs deployed around the Luzon Strait in 2018–2019 (12 deployed east of Taiwan within a 3 × grid) were used to reveal the three-dimensional structure of mesoscale eddies and their interaction with Kuroshio. The results show a strengthening (weakening) of the tilt of the pycnocline, which has also caused a deeper (shallower) pycnocline in eastern Taiwan following an anticyclonic (cyclonic) interaction with Kuroshio, which resulted in a strengthening (weakening) of the Kuroshio. During the anticyclonic eddy impinging Kuroshio, the downward (upward) movement at the center of the anticyclonic eddy (Kuroshio) results in a positive (negative) anomaly structure for temperature, with corresponding positive (negative) anomalies for salinity above 600 m in the intermediate layer and negative (positive) anomalies below 600 m. In contrast, when the cyclonic eddies interact with the Kuroshio, the temperature and salinity anomalies change simultaneously, with the temperature showing an overall negative anomaly and the salinity showing a negative and positive anomaly above and below 600 m, respectively. The research in this study provides the basis for further research on energy exchange during eddy–Kuroshio interactions.

Enhanced production of sugars and UV-shielded lignin/PAN fiber mats from chemi-mechanical pulps - Lei Wang; Xiaohan Li; Chenzhong Wan; Kesheng Zhang; Zhao Wu; Fen Hu; Ran Zhang; Xiao Fu; Hongbo Yu (Science of The Total Environment, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

One-dimensional fiber beam-column model and two-dimensional fixed crack model for numerical simulation of UHPC structures - Xiao-Wen Hu; Ran Ding; Zi-Yu Zhang; Jian-Sheng Fan (Engineering Structures, 2023)

Ectopic expression of MmCYP1A1, a mouse cytochrome P450 gene, positively regulates stress tolerance in apple calli and Arabidopsis - Xiao-Na Wang; Fei Yang; Jiu-Cheng Zhang; Yi-Ran Ren; Jian-Ping An; Da-Yong Chang; Xiao-Fei Wang; Chun-Xiang You (Plant Cell Reports, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

The pre-addition of “blocking” proteins decreases subsequent cellulase adsorption to lignin and enhances cellulose hydrolysis - Jingyun Liu; Jie Wu; Yi Lu; Huaiyu Zhang; Qi Hua; Ran Bi; Orlando Rojas; Scott Renneckar; Senqing Fan; Zeyi Xiao; Jack Saddler (Bioresource Technology, 2023)

Effect of salinity on greenhouse gas production and emission in marsh soils during the decomposition of wetland plants - Ju Zhang; Jim Jian Wang; Ran Xiao; Huanguang Deng; Ronald D. DeLaune (Journal of Soils and Sediments, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

The roles of ETS transcription factors in liver fibrosis - Li-Ye Zhang; Yong Tan; Xiao-Jie Luo; Jiang-Feng Wu; Yi-Ran Ni (Human Cell, 2022)

Intensive stretch-activated CRT-PMCA1 feedback loop promoted apoptosis of myoblasts through Ca2+ overloading - Dapeng Ren; Ran liu; Xiao Yan; Qiang Zhang; Xuemin Zeng; Xiao Yuan (Apoptosis, 2022)

Endovascular Therapy for Symptomatic Intracranial Artery Stenosis: a Systematic Review and Network Meta-analysis - Tao Wang; Kun Yang; Xiao Zhang; Jichang Luo; Ran Xu; Xue Wang; Yutong Yang; Xuesong Bai; Yan Ma; Yuxiang Yan; Liqun Jiao (Translational Stroke Research, 2022)

Extracellular histones induce inflammation and senescence of vascular smooth muscle cells by activating the AMPK/FOXO4 signaling pathway - Hang Yang; Yong-Yan Luo; Lue-Tao Zhang; Kai-Ran He; Xiao-Jun Lin (Inflammation Research, 2022)

Three new unsaturated fatty acids from marine-derived fungus Aspergillus sp. SCAU150 - Ting Zhao; Xiao-Yong Zhang; Ran-Sha Deng; Zhen Tan; Guang-Ying Chen; Xu-Hua Nong (Natural Product Research, 2022)

Parkinson’s Disease and Ischemic Stroke: a Bidirectional Mendelian Randomization Study - Shiyuan Fang; Xinzhi Hu; Tao Wang; Yutong Yang; Ran Xu; Xiao Zhang; Jichang Luo; Yan Ma; Aman B. Patel; Adam A. Dmytriw; Liqun Jiao (Translational Stroke Research, 2022)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Interleukin-17A Contributed to the Damage of Blood-CNS Barriers During Streptococcus suis Meningitis - Lei Xu; Xi Lu; Peng Xiao; Ran Liu; Kunlong Xia; Meizhou Wu; Meilin Jin; Anding Zhang (Molecular Neurobiology, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Editing arcs to improve the capacity of GNSS-IR for soil moisture retrieval in undulating terrains - Qishun Ran; Bao Zhang; Yibin Yao; Xiao Yan; Junyu Li (GPS Solutions, 2022)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Human activity and climate change triggered the expansion of rocky desertification in the karst areas of Southwestern China - Chaojun Chen; Daoxian Yuan; Hai Cheng; Tsailuen Yu; Chuanchou Shen; R. Lawrence Edwards; Yao Wu; Siya Xiao; Jian Zhang; Tao Wang; Ran Huang; Ziqi Liu; et al. (Science China Earth Sciences, 2021)

Elabela prevents angiotensin II-induced apoptosis and inflammation in rat aortic adventitial fibroblasts via the activation of FGF21–ACE2 signaling - Juan-Juan Song; Mei Yang; Ying Liu; Jia-Wei Song; Xiao-Yan Liu; Ran Miao; Zhen-Zhou Zhang; Yu Liu; Yi-Fan Fan; Qian Zhang; Ying Dong; Xin-Chun Yang; et al. (Journal of Molecular Histology, 2021)

Molecular Evolution of Tooth-Related Genes Provides New Insights into Dietary Adaptations of Mammals - Yuan Mu; Ran Tian; Linlin Xiao; Di Sun; Zepeng Zhang; Shixia Xu; Guang Yang (Journal of Molecular Evolution, 2021)
Mammals have evolved different tooth phenotypes that are hypothesized to be associated with feeding habits. However, the genetic basis for the linkage has not been well explored. In this study, we investigated 13 tooth-related genes, including seven enamel-related genes ( AMELX , AMBN , ENAM , AMTN , ODAM , KLK4 and MMP20 ) and six dentin-related genes ( DSPP , COL1A1 , DMP1 , IBSP , MEPE and SPP1 ), from 63 mammals to determine their evolutionary history. Our results showed that different evolutionary histories have evolved among divergent feeding habits in mammals. There was stronger positive selection for eight genes ( ENAM , AMTN , ODAM , KLK4 , DSPP , DMP1 , COL1A1 , MEPE ) in herbivore lineages. In addition, AMELX , AMBN , ENAM , AMTN , MMP20 and COL1A1 underwent accelerated evolution in herbivores. While relatively strong positive selection was detected in IBSP , SPP1 , and DSPP , accelerated evolution was only detected for MEPE and SPP1 genes among the carnivorous lineages. We found positive selection on AMBN and ENAM genes for omnivorous primates in the catarrhini clade. Interestingly, a significantly positive association between the evolutionary rate of ENAM , ODAM , KLK4 , MMP20 and the average enamel thickness was found in primates. Additionally, we found molecular convergence in some amino acid sites of tooth-related genes among the lineages whose feeding habit are similar. The positive selection of related genes might promote the formation and bio-mineralization of tooth enamel and dentin, which would make the tooth structure stronger. Our results revealed that mammalian tooth-related genes have experienced variable evolutionary histories, which provide some new insights into the molecular basis of dietary adaptation in mammals.

KCNQ Channels in the Mesolimbic Reward Circuit Regulate Nociception in Chronic Pain in Mice - Hao-Ran Wang; Su-Wan Hu; Song Zhang; Yu Song; Xiao-Yi Wang; Lei Wang; Yang-Yang Li; Yu-Mei Yu; He Liu; Di Liu; Hai-Lei Ding; Jun-Li Cao (Neuroscience Bulletin, 2021)
Mesocorticolimbic dopaminergic (DA) neurons have been implicated in regulating nociception in chronic pain, yet the mechanisms are barely understood. Here, we found that chronic constructive injury (CCI) in mice increased the firing activity and decreased the KCNQ channel-mediated M-currents in ventral tegmental area (VTA) DA neurons projecting to the nucleus accumbens (NAc). Chemogenetic inhibition of the VTA-to-NAc DA neurons alleviated CCI-induced thermal nociception. Opposite changes in the firing activity and M-currents were recorded in VTA DA neurons projecting to the medial prefrontal cortex (mPFC) but did not affect nociception. In addition, intra-VTA injection of retigabine, a KCNQ opener, while reversing the changes of the VTA-to-NAc DA neurons, alleviated CCI-induced nociception, and this was abolished by injecting exogenous BDNF into the NAc. Taken together, these findings highlight a vital role of KCNQ channel-mediated modulation of mesolimbic DA activity in regulating thermal nociception in the chronic pain state.

Biotransformation of Phlorizin by Eurotium cristatum to Increase the Antioxidant and Antibacterial Activity of Docynia indica Leaves - Jie Xie; Jiang Chen; Xue-ran Mei; Ming-jun Zhu; Xue-li Li; Juan Du; Xiao-yu Zhang (Current Microbiology, 2021)

Transcriptome sequencing and analysis for the pigmentation of scale and skin in common carp (Cyprinus carpio) - Yu-Jie Zhao; Jun Xiao; Mei-Di Huangyang; Ran Zhao; Qi Wang; Yan Zhang; Jiong-Tang Li (Molecular Biology Reports, 2021)

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Characterization of phosphorus engineered biochar and its impact on immobilization of Cd and Pb from smelting contaminated soils - Jing Ren; Zixuan Zhao; Amjad Ali; Weidou Guan; Ran Xiao; Jim J. Wang; Sirui Ma; Di Guo; Baoyue Zhou; Zengqiang Zhang; Ronghua Li (Journal of Soils and Sediments, 2020)

Nitratireductor mangrovi sp. nov., a Nitrate-Reducing Bacterium Isolated from Mangrove Soil - Yanghui Ye; Cen Yan; Yanfang Nie; Jianwei Zhang; Zhe Zhao; Ran Zhang; Chuan Xiao; Min Wu (Current Microbiology, 2020)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

Enhanced removal of phosphate and ammonium by MgO-biochar composites with NH3·H2O hydrolysis pretreatment - Ran Xiao; Han Zhang; Zhineng Tu; Ronghua Li; Songling Li; Zhongyang Xu; Zengqiang Zhang (Environmental Science and Pollution Research, 2020)

Population genetic structure of Thryssa kammalensis in the Chinese Seas inferred from control region sequences - Jing Zhang; Nan Zhang; Yuan Li; Jiaguang Xiao; Ran Zhang; Tianxiang Gao; Longshan Lin (Marine Biodiversity, 2019)

A rapid and scalable integrated membrane separation process for purification of polysaccharides from Enteromorpha prolifera - Wenyao Shao; Huan Zhang; Ran Duan; Quanling Xie; Zhuan Hong; Zongyuan Xiao (Natural Product Research, 2019)

Effects of β-Cyclodextrin and Hydroxypropyl-β-Cyclodextrin Inclusions on the Degradation of Magnolol by Intestinal Bacteria - Lan Tang; Zhuanfeng Zhu; Miao Xie; Lipeng Cao; Xiao Lan Yu; Ran Zhang; Zhimin Ou; Weiguang Shan; Zhenhai Zhang (AAPS PharmSciTech, 2019)

Interleukin-26 upregulates interleukin-22 production by human CD4+ T cells in tuberculous pleurisy - Min Zhang; Yi-Ran Niu; Jing-Yuan Liu; Xiao-Shan Wei; Xiao-Rong Wang; Lin-Lin Ye; Wen-Bei Peng; Jian-Chu Zhang; Xiao-Nan Tao; Qiong Zhou (Journal of Molecular Medicine, 2019)

A life support-based comprehensive treatment regimen dramatically lowers the in-hospital mortality of patients with fulminant myocarditis: a multiple center study - Sheng Li; Shengyong Xu; Chenze Li; Xiao Ran; Guanglin Cui; Mengying He; Kun Miao; Chunxia Zhao; Jiangtao Yan; Rutai Hui; Ning Zhou; Yan Wang; et al. (Science China Life Sciences, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Quantitative Structure-Property Relationship for pH-Triggered Drug Release Performance of Acid-Responsive Four/Six-Arms Star Polymeric Micelles - Ran Zhang; Li-yang Wen; Wen-sheng Wu; Xiao-zhe Yuan; Li-juan Zhang (Pharmaceutical Research, 2019)

Identification of drug target candidates of the swine pathogen Actinobacillus pleuropneumoniae by construction of protein–protein interaction network - Siqi Li; Zhipeng Su; Chengjun Zhang; Zhuofei Xu; Xiaoping Chang; Jiawen Zhu; Ran Xiao; Lu Li; Rui Zhou (Genes & Genomics, 2018)

Genetic mapping and salt tolerance of a novel D1-allelic mutant of rice (Oryza sativa L.) - Wei-jiang Tian; Xiao-qiong Zhang; Xiao-wen Wang; Jia Xie; Yang-yang Li; Ying Sun; Yi-ran Tao; Yu-zhen Xiong; Xian-chun Sang (Acta Physiologiae Plantarum, 2018)

Amyloid β-Derived Diffusible Ligands (ADDLs) Induce Abnormal Autophagy Associated with Aβ Aggregation Degree - Jie Wen; Fang Fang; Shu-Han Guo; Ying Zhang; Xiang-Lei Peng; Wei-Min Sun; Xiao-Ran Wei; Jin-Sheng He; Tao Hung (Journal of Molecular Neuroscience, 2018)

Monazite behaviour during isothermal decompression in pelitic granulites: a case study from Dinggye, Tibetan Himalaya - Jia-Min Wang; Fu-Yuan Wu; Daniela Rubatto; Shi-Ran Liu; Jin-Jiang Zhang; Xiao-Chi Liu; Lei Yang (Contributions to Mineralogy and Petrology, 2017)

Ultrastructure of ellipsoidal magnetotactic multicellular prokaryotes depicts their complex assemblage and cellular polarity in the context of magnetotaxis - Pedro Leão; Yi‐Ran Chen; Fernanda Abreu; Mingling Wang; Wei‐Jia Zhang; Ke Zhou; Tian Xiao; Long‐Fei Wu; Ulysses Lins (Environmental Microbiology, 2017)
Summary Magnetotactic multicellular prokaryotes (MMPs) consist of unique microorganisms formed by genetically identical Gram‐negative bacterial that live as a single individual capable of producing magnetic nano‐particles called magnetosomes. Two distinct morphotypes of MMPs are known: spherical MMPs (sMMPs) and ellipsoidal MMPs (eMMPs). sMMPs have been extensively characterized, but less information exists for eMMPs. Here, we report the ultrastructure and organization as well as gene clusters responsible for magnetosome and flagella biosynthesis in the magnetite magnetosome producer eMMP Candidatus Magnetananas rongchenensis. Transmission electron microscopy and focused ion beam scanning electron microscopy (FIB‐SEM) 3D reconstruction reveal that cells with a conspicuous core‐periphery polarity were organized around a central space. Magnetosomes were organized in multiple chains aligned along the periphery of each cell. In the partially sequenced genome, magnetite‐related mamAB gene and mad gene clusters were identified. Two cell morphologies were detected: irregular elliptical conical ‘frustum‐like’ (IECF) cells and H‐shaped cells. IECF cells merge to form H‐shaped cells indicating a more complex structure and possibly a distinct evolutionary position of eMMPs when compared with sMMPs considering multicellularity.

Modeling and Manufacturing Technology for Personalized Biological Fixed Implants - Zhang Guoqing; Yang Yongqiang; Lin Hui; Song Changhui; Xiao Ran; Yu Jiakuo (Journal of Medical and Biological Engineering, 2017)

Isolation of a new cytotoxic polyhydroxysterol from the South China Sea soft coral Sinularia sp. - Huan Sun; Fen Liu; Mei-Ran Feng; Qi Peng; Xiao-Jian Liao; Ting-Ting Liu; Jun Zhang; Shi-Hai Xu (Natural Product Research, 2016)

A new sesquiterpene from the gorgonian coral Menella sp. - Qi Peng; Fen Liu; Huan Sun; Xiao-Jian Liao; Mei-Ran Feng; Ting-Ting Liu; Zheng-Xiong Xu; Jun Zhang; Shi-Hai Xu (Natural Product Research, 2016)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

Fragment virtual screening based on Bayesian categorization for discovering novel VEGFR-2 scaffolds - Yanmin Zhang; Yu Jiao; Xiao Xiong; Haichun Liu; Ting Ran; Jinxing Xu; Shuai Lu; Anyang Xu; Jing Pan; Xin Qiao; Zhihao Shi; Tao Lu; et al. (Molecular Diversity, 2015)

Sam68 Promotes NF-κB Activation and Apoptosis Signaling in Articular Chondrocytes during Osteoarthritis - Libin Xu; Chi Sun; Sihui Zhang; Xinbao Xu; Leilei Zhai; Youhua Wang; Shitao Wang; Zhongbing Liu; Hongbing Cheng; Min Xiao; Ran Tao; Dongmei Zhang (Inflammation Research, 2015)

Odontoblast β-catenin signaling regulates fenestration of mouse Hertwig’s epithelial root sheath - Ran Zhang; Yan Teng; Liang Zhu; JingTing Lin; Xiao Yang; Guan Yang; TieJun Li (Science China Life Sciences, 2015)

Genome-wide characterization and analysis of F-box protein-encoding genes in the Malus domestica genome - Hao-Ran Cui; Zheng-Rong Zhang; Wei lv; Jia-Ning Xu; Xiao-Yun Wang (Molecular Genetics and Genomics, 2015)

Short-term changes in total heavy metal concentration and bacterial community composition after replicated and heavy application of pig manure-based compost in an organic vegetable production system - Wei Tian; Zhenhua Zhang; Xiaofeng Hu; Ran Tian; Jibing Zhang; Xingji Xiao; Yunguan Xi (Biology and Fertility of Soils, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

True-amplitude wavefield separation using staggered-grid interpolation in the wavenumber domain - Qi-Zhen Du; Ming-Qiang Zhang; Xiao-Ran Chen; Xu-Fei Gong; Cheng-Feng Guo (Applied Geophysics, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Vibrio harveyi as a causative agent of mass mortalities of megalopa in the seed production of swimming crab Portunus trituberculatus - Xiao-Jun Zhang; Xue-Song Bai; Bin-Lun Yan; Ke-Ran Bi; Lei Qin (Aquaculture International, 2014)

Analysis of quality factors for Rayleigh channel waves - Xiao-Hui Yang; Si-Yuan Cao; De-Chun Li; Peng-Fei Yu; Hao-Ran Zhang (Applied Geophysics, 2014)

An efficient multistep ligand-based virtual screening approach for GPR40 agonists - Sihui Yao; Tao Lu; Zifan Zhou; Haichun Liu; Haoliang Yuan; Ting Ran; Shuai Lu; Yanmin Zhang; Zhipeng Ke; Jinxing Xu; Xiao Xiong; Yadong Chen (Molecular Diversity, 2014)

Enhanced viability of Lactobacillus reuteri for probiotics production in mixed solid-state fermentation in the presence of Bacillus subtilis - Yi-Ran Zhang; Hai-Rong Xiong; Xiao-Hua Guo (Folia Microbiologica, 2014)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Natural populations of lactic acid bacteria in douchi from Yunnan Province, China - Chen-jian Liu; Fu-ming Gong; Xiao-ran Li; Hai-yan Li; Zhong-hua Zhang; Yue Feng; Hiroko Nagano (Journal of Zhejiang University-SCIENCE B, 2012)

Molecular cloning and its expression of trachealess gene (As-trh) during development in brine shrimp, Artemia sinica - Jia-Qing Wang; Lin Hou; Nan Yi; Riu-Feng Zhang; Xiang-Yang Zou; Qin Xiao; Ran Guo (Molecular Biology Reports, 2012)

Chemical composition and antioxidant activity of the essential oil of endemic Viola tianshanica - Jin Yang; Zhen Qu; Yu-Ling Xiao; Guo-Fu Qiu; Tao Zhang; Zhong-Yuan Wu; Xian-Ran He; Xian-Ming Hu (Natural Product Research, 2011)

Effects of the Metals Lead and Zinc on the Growth, Development, and Reproduction of Pardosa Astrigera (Araneae: Lycosidae) - Xiao-qiong Chen; Zheng-tian Zhang; Ran Liu; Xiu-Ling Zhang; Jian Chen; Yu Peng (Bulletin of Environmental Contamination and Toxicology, 2011)

An easy-to-use site-directed mutagenesis method with a designed restriction site for convenient and reliable mutant screening - Bao-zhong Zhang; Xin Zhang; Xiao-ping An; Duo-liang Ran; Yu-sen Zhou; Jun Lu; Yi-gang Tong (Journal of Zhejiang University-SCIENCE B, 2009)

Analysis of Prevalence and Risk Factors of Hypertension Among Uygur Adults in Tushala and Hetian Xinjiang Uygur Autonomous Region - Lin-Lin Li; Xiao-Yan Liu; Jian-Xin Ran; Ye Wang; Xin Luo; Tao Wang; Jun Ren; Mayinuer Aisha; Rebiya Abudureheman; Adalaiti Xiawudong; Xiao-Chun Zhang; Xin-Min Mao (Cardiovascular Toxicology, 2008)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)